What childhood obesity prevention programmes work? A systematic review and meta‐analysis. Issue 7 (20th April 2015) - Wang, Y.; Cai, L.; Wu, Y.; Wilson, R. F.; Weston, C.; Fawole, O.; Bleich, S. N.; Cheskin, L. J.; Showell, N. N.; Lau, B. D.; Chiu, D. T.; Zhang, A.; et al.
Summary Previous reviews of childhood obesity prevention have focused largely on schools and findings have been inconsistent. Funded by the US Agency for Healthcare Research and Quality (AHRQ) and the National Institutes of Health, we systematically evaluated the effectiveness of childhood obesity prevention programmes conducted in high‐income countries and implemented in various settings. We searched MEDLINE®, Embase, PsycINFO, CINAHL®, ClinicalTrials.gov and the Cochrane Library from inception through 22 April 2013 for relevant studies, including randomized controlled trials, quasi‐experimental studies and natural experiments, targeting diet, physical activity or both, and conducted in children aged 2–18 in high‐income countries. Two reviewers independently abstracted the data. The strength of evidence (SOE) supporting interventions was graded for each study setting (e.g. home, school). Meta‐analyses were performed on studies judged sufficiently similar and appropriate to pool using random effect models. This paper reported our findings on various adiposity‐related outcomes. We identified 147 articles (139 intervention studies) of which 115 studies were primarily school based, although other settings could have been involved. Most were conducted in the United States and within the past decade. SOE was high for physical activity‐only interventions delivered in schools with home involvement or combined diet–physical activity interventions delivered in schools with both home and community components. SOE was moderate for school‐based interventions targeting either diet or physical activity, combined interventions delivered in schools with home or community components or combined interventions delivered in the community with a school component. SOE was low for combined interventions in childcare or home settings. Evidence was insufficient for other interventions. In conclusion, at least moderately strong evidence supports the effectiveness of school‐based interventions for preventing childhood obesity. More research is needed to evaluate programmes in other settings or of other design types, especially environmental, policy and consumer health informatics‐oriented interventions.